Advertising Cost Interactions and the Optimality of Pulsing - Hahn, Minhi; Hyun, Jin-Sok (Management Science, 1991)
Whether pulsing, other than chattering, can be optimal is an important concern to both advertising practitioners and marketing scientists. In this paper, we explicitly incorporate various types of costs to a one-state advertising model to analyze the effect of these costs on the optimal advertising policy. We prove that the interaction of fixed and pulsing costs does make pulsing optimal under a reasonable condition. This result not only identifies an important factor that leads to the optimality of pulsing, but also generalizes the finding obtained by Sasieni (1971).